Exemplary Learning of Santri's Morals Based on Live Media and Graphic Media: Pembelajaran Keteladanan Akhlak Santri Berbasis Media Langsung dan Media Grafis - Siregar, Muhammad Fajar Rasyiid; Halimah, Siti; Budianti, Yusnaili (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Moral character (akhlak) formation in students is a critical objective in Islamic education, requiring both cognitive and affective engagement. Specific Background: Visual and spiritual educational methods, such as graphic design and dhikr practices, are increasingly recognized for their potential to influence students' behavior and values. Knowledge Gap: However, empirical research examining the combined effects of these methods on moral character, particularly in Islamic boarding school settings, remains limited. Aim: This study aims to investigate the influence of exemplary learning through graphic design and dhikr practices on the moral character of students at Rubath Adz-Dzikra Lil Mu’minin. Results: Utilizing a quantitative approach with simple and multiple regression analyses, the study found that graphic design-based learning contributed 22.5%, dhikr practices 21.1%, and both simultaneously 41.6% to the development of students’ moral character, with model significance confirmed via F-test. Novelty: The integration of visual and spiritual pedagogies provides a novel framework for moral education. Implications: These findings suggest that educators in Islamic boarding schools should adopt holistic approaches, combining visual and spiritual methods, to effectively nurture moral character in students. Highlights: Combines visual and spiritual methods for character education. Graphic design and dhikr significantly influence students’ akhlak. Recommends integrated approaches in Islamic boarding schools. Keywords: Exemplary Learning, Graphic Design, Dhikr Practices, Moral Character, Islamic Education